Multidões agroecológicas emergentes na agricultura urbana das encostas de Medellín - Velásquez Castañeda, Carlos Alberto (Universidade Federal de São Carlos, 2026)
In the popular comunas located on the hillsides of Medellín (Colombia), the self-construction of territory coexists with food insecurity, land-use disputes, and recurring risks, while also sustaining dense organizational networks. From a perspective situated in the Global South, this research examines how urban agriculture consolidates and to what extent it strengthens social cohesion and collective action, beyond a strictly productivist framing. The study focuses on practices and organizational processes linked to family and community gardens in Medellín’s Northeastern Urban–Rural Edge (BUR NOR), drawing on the Agroecological Multitudes approach (Giraldo, 2022) to analyze articulations across environmental/territorial, social/organizational, and political dimensions. Methodologically, the research adopts Participatory Action Research, combining semi-structured interviews, focus groups, participant observation, and documentary analysis. The findings indicate that urban and popular agroecology operates as a strategy for territorial defense, generating networks of solidarity and political advocacy. Its hybrid character becomes evident (between reterritorialized ruralities and urban dynamics, and between community autonomy and institutional dependence) reinforcing the centrality of community organization for its continuity.
Emerging agroecological multitudes in urban agriculture on the hillsides of Medellín
Multitudes agroecológicas emergentes en la agricultura urbana de las laderas de Medellín
Keywords: Ação coletiva; Agroecologia urbana; Multidões agroecológicas; Multifuncionalidade agricultura urbana; Collective action; Urban agroecology; Agroecological multitudes; Multifunctionality of urban agriculture; Acción colectiva; Agroecología urbana; Multitudes agroecológicas; Multifuncionalidad agricultura urbana; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA DO DESENVOLVIMENTO; 1. Erradicação da Pobreza; 2. Fome Zero e Agricultura Sustentável; 11. Cidades e Comunidades Sustentáveis; 13. Ação contra a Mudança Global do Clima